2008
DOI: 10.1021/ac800892h
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Cortisol in Saliva with a Flow-Filtered, Portable Surface Plasmon Resonance Biosensor System

Abstract: Saliva provides a useful and non-invasive alternative to blood for many biomedical diagnostic assays. The level of the hormone cortisol in blood and saliva is related to the level of stress. We present here the development of a portable surface plasmon resonance (SPR) biosensor system for detection of cortisol in saliva. Cortisol-specific monoclonal antibodies were used to develop a competition assay with a 6-channel portable SPR biosensor designed in our laboratory. The detection limit of cortisol in laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
124
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(130 citation statements)
references
References 27 publications
6
124
0
Order By: Relevance
“…Previous initial studies showed that the AuNP assay with 15-1 responded to the stress biomarker cortisol, but not to two other markers of stress, epinephrine and norepinephrine, or cholic acid, a marker of liver disease structurally similar to cortisol 24 . The response was observed in the normal range of free cortisol reported in human serum (~150-600 nM) 6 , validating that the aptamer selected for a structural change upon cortisol binding produces a response in the AuNP assay. In this current work, characterization of the system was taken one step further by adjusting the coverage (density) of 15 .…”
Section: -3 Ggaatggatccacatccatgggagggttggaagggaggggcccggggtgggccatsupporting
confidence: 59%
See 3 more Smart Citations
“…Previous initial studies showed that the AuNP assay with 15-1 responded to the stress biomarker cortisol, but not to two other markers of stress, epinephrine and norepinephrine, or cholic acid, a marker of liver disease structurally similar to cortisol 24 . The response was observed in the normal range of free cortisol reported in human serum (~150-600 nM) 6 , validating that the aptamer selected for a structural change upon cortisol binding produces a response in the AuNP assay. In this current work, characterization of the system was taken one step further by adjusting the coverage (density) of 15 .…”
Section: -3 Ggaatggatccacatccatgggagggttggaagggaggggcccggggtgggccatsupporting
confidence: 59%
“…This implies that the detection range for the target of interest can be adjusted based on optimizing the DNA surface coverage in the AuNP assay. This could be beneficial when comparing, for example, the range of free cortisol in human serum (~150-600 nM) versus human saliva (~5-25 nM) 6,37 . While physiological fluids are far more complex than this buffer assay, the results provide an extension on the proof-of-principle work demonstrating that AuNP conditions can be adjusted depending on the application, and that further work towards broadening the medium to biological fluids would be of interest to the biosensor community.…”
Section: -3 Ggaatggatccacatccatgggagggttggaagggaggggcccggggtgggccatmentioning
confidence: 99%
See 2 more Smart Citations
“…Because our system is label-free and, thus, prone to be sensitive to nonspecific binding, FBS was filtered with a 3 kDa cutoff membrane in order to remove most of the proteins in the serum (see Experimental Section). 10 Tobramycin concentrations within the clinical analytical range (10,20,40,60, and 80 μM; clinical range of 0.5−80 μM) were then spiked in FBS, filtered, and injected at 10 μL/min over the sensing areas in order to be measured with the T-LSPR measurement system (Figure 8). The data were normalized for baseline drift and response variations by the signal corresponding to the regeneration injection (NaCl 1M, entirely bulk effect).…”
Section: Analytical Chemistrymentioning
confidence: 99%